Sie sind auf Seite 1von 5

HW-10-solution

1. M&T Prob. 12-1


The equations of motions for the two blocks are
mx1 + k1 x1 + k12 ( x1 − x2 ) = 0
mx2 + k 2 x 2 + k12 ( x 2 − x1 ) = 0
Let x1 = Ae − iωt , x2 = Be −iωt . Then the equations of motions are
(−mω 2 + k1 + k12 ) A − k12 B = 0
− k12 A + (− mω 2 + k 2 + k12 ) B = 0
The non-zero solution is determined by
 − mω 2 + k1 + k12 − k12 
det 
 − k12 − mω + k 2 + k12 
2

= (− mω 2 + k1 + k12 )(− mω 2 + k 2 + k12 ) − k122 = 0


k + k + 2k12 2 k1 k12 + k 2 k12 + k1 k 2
ω2 − 1 2 ω + = 0 . The two solutions are
m m2
2 2
k + k + 2k12  k − k 2   k12 
ω = 1 2
2
1 −  1  + 
2m  2m   m 
2 2
k + k + 2k12  k − k 2   k12 
ω = 1 2
2
2 +  1  + 
2m  2m   m 
Assuming k1≤k2,
2 2 2 2 2 2
 k12   k − k 2   k12   k − k 2   k12   k − k1  k12   k 2 − k1 + 2k12 
  ≤ 1  +  ≤ 1  +  + 2 2  = 
 m  2m   m   2m   m   2 m  m   2m 

2 2
k  k − k 2   k12  k − k1 + 2k12
or 12 ≤  1  +  ≤ 2 .
m  2m   m  2m
Therefore we have
2 2
k1 + k 2 + 2k12 k12 k1 + k 2 + 2k12  k − k 2   k12  k + k 2 + 2k12 k 2 − k1 + 2k12
− ≥ −  1  +  ≥ 1 −
2m m 2m  2m   m  2m 2m

k1 + k 2 k
or ≥ ω 12 ≥ 1 , and
2m m
2 2
k1 + k 2 + 2k12 k12 k1 + k 2 + 2k12  k − k 2   k12  k + k 2 + 2k12 k 2 − k1 + 2k12
+ ≤ +  1  +  ≤ 1 +
2m m 2m  2m   m  2m 2m

k1 + k 2 2k12 k + k12
or + ≤ ω 22 ≤ 2 .
2m m m
k1 k + k 2 k1 + k 2 2k12 k + k12
All together ≤ ω 12 ≤ 1 ≤ + ≤ ω 22 ≤ 2 .
m 2m 2m m m

2. M&T Prob. 12-6


The equations of motion for the two blocks are
mx1 + β ( x1 − x 2 ) + kx1 = 0
mx2 + β ( x 2 − x1 ) + kx 2 = 0
Let x1 = Re( Ae − iωt ), x 2 = Re( Be − iωt ) . Then the equations of motions are
( − mω 2 + k − iωβ ) A + iωβ B = 0 (1)
iωβ A + ( − mω 2 + k − iωβ ) B = 0 (2)
The non-zero solutions are determined by ( − mω 2 + k − iωβ ) 2 − (iωβ ) 2 = 0 .
k iβ k β2
Thus ω = , ω 2 = − ±
2
1
2
− .
m m m m2
k  k 
(a) For ω 12 = , eqn(1) gives A=B. Thus x1 = x 2 = A cos t + φ  .
m  m 
iβ k β2
(b) For ω = − ±
2
2 − , eqn (1) gives A=-B. Thus
m m m2

βt  k β2 
x1 = − x 2 = Ae m cos − 2 t +φ.
 m m 
 

3. M&T Prob. 12-11


Let q1 = q10 e − iωt , q2 = q20 e − iωt so that I 1 = qD1 = −iωq10 e − iωt , I 2 = qD 2 = −iωq20 e − iωt .
Then the Kirchhoff equations become
 1
 − Lω +  q10 − Mω q 20 = 0
2 2

 C  (1)
 1
− Mω 2 q10 +  − Lω 2 + q 20 = 0 (2)
 C
2
 1
The non-zero solutions are determined by  − Lω 2 +  − Mω 2 ( )2
= 0 . This gives
 C
1 1
ω1 = ,ω 2 = .
C(L − M ) C(L + M )

4. M&T Prob. 12-16.


2R
co
s( Rα
θ α /2
)
θ2Rcos( α /2)
α/2
α

The velocity of M relative to the hoop is RαD . The velocity of the hoop at the position
α
of M is θD 2 R cos . This gives the velocity of mass M to be
2
α α
v 2 = R 2αD 2 + θD 2 4 R 2 cos 2 + 4 R 2αDθD cos 2 .
2 2
The kinetic energy is
1 1 1  α α
T = 2 MR 2θD 2 + Mv 2 = MR 2αD 2 + MR 2 1 + 2 cos 2 θD 2 + 2 MR 2αDθD cos 2 .
2 2 2  2 2
The potential energy is
U = − MgR cosθv − Mg[ R cosθ + R cos(θ + α )] = −2 MgR cosθv − MgR cos(θ + α ) .
L = T −U
1  α α
= MR 2αD 2 + MR 2 1 + 2 cos 2 θD 2 + 2 MR 2αDθD cos 2 + 2 MgR cosθ + MgR cos(θ + α )
2  2 2
d  ∂L  ∂L d  ∂L  ∂L
 − = 0 and  − = 0 give
dt  ∂αD  ∂α dt  ∂θD  ∂θ
α α α α α α α g
αDD + 2θDD cos 2 − 2θDαD cos sin + 2 cos sin θD 2 + 2αDθD cos sin + sin(θ + α ) = 0
2 2 2 2 2 2 2 R
 α  α α α α α 2g g
21 + 2 cos 2 θDD − 4αDθD cos sin + 2αDD cos 2 − 2αD 2 cos sin + sin θ + sin(θ + α ) = 0
 2 2 2 2 2 2 R R

For small θ and α, these two equations become


g
α + 2θ + (θ + α ) = 0
R
3g g
6θ + 2α + θ + α = 0
R R
Let α = α 0 e , θ = θ 0 e − iωt , we have
− iωt

 g  g
 − ω + α 0 +  − 2ω + θ 0 = 0
2 2
(1)
 R  R
 g  3g 
 − 2ω + α 0 +  − 6ω + θ 0 = 0
2 2
(2)
 R  R
The non-zero solution is determined by
2
 g  3g   g
 − ω +  − 6ω +  −  − 2ω +  = 0 .
2 2 2

 R  R  R
2g 2 g
The solutions are ω 12 = ,ω 2 = .
R 2R
2g
(a) For ω 1 = , eqn (1) gives α 0 = 3θ 0 .
R
g
(b) For ω 2 = , eqn (1) gives α 0 = 0 .
2R

5. M&T Prob. 12-21


mx 2 mx 2 mx 2 1
L = 1 + 2 + 3 − [k1 ( x12 + x32 ) + k 2 x 22 + k 3 ( x1 x 2 + x 2 x3 )] .
2 2 2 2
The equations of motions are
k x
mDxD1 + k1 x1 + 3 2 = 0
2
k3
mDxD2 + k 2 x 2 + ( x1 + x3 ) = 0
2
k 3 x2
mDxD3 + k1 x3 + =0
2

Let x1 = Ae − iωt , x 2 = Be − iωt , x3 = Ce − iωt . The equations of motions become


k
(−mω 2 + k1 ) A + 3 B = 0 (1)
2
k3 k
A + (− mω 2 + k 2 ) B + 3 C = 0 (2)
2 2
k3
B + (− mω 2 + k1 )C = 0 (3)
2
The non-zero solution is determined by
 k3 
 − mω 2 + k1 0 
 2 
det  k3
− mω + k 2
2 k3 
 2 2 
 k3 
 0 − mω 2 + k1 
 2 
k
= (− mω 2 + k1 )[m 2ω 4 − m(k1 + k 2 )ω 2 + k1k 2 − 3 ] = 0
2
With k 3 = 2k1k 2 , (− mω + k1 )ω [m ω − m(k1 + k 2 )] = 0 .
2 2 2 2

k1 k1 + k 2
The three solutions are ω 1 = , ω 2 = 0, ω 3 = .
m m
k1
(a) For ω 1 = , eqn (1) gives B=0, and eqn (2) gives A=-C.
m
k
(b) For ω 2 = 0 , eqn (1)-(3) give A = − 2 B = C . Under this condition, the
2 k1
potential energy remains constant. That's why ω=0.
k + k2 k2
(c) For ω 3 = 1 , eqn (1)-(3) give A = B =C.
m 2 k1